Toxin B Variants from Clostridium difficile Strains VPI 10463 and NAP1/027 Share Similar Substrate Profile and Cellular Intoxication Kinetics but Use Different Host Cell Entry Factors - López Ureña, Diana (2019)
Clostridium difficile induces antibiotic-associated diarrhea due to the release of toxin A (TcdA) and toxin B (TcdB), the latter being its main virulence factor. The epidemic strain NAP1/027 has an increased virulence attributed to different factors. We compared cellular intoxication by TcdBNAP1 with that by the reference strain VPI 10463 (TcdBVPI). In a mouse ligated intestinal loop model, TcdBNAP1 induced higher neutrophil recruitment, cytokine release, and epithelial damage than TcdBVPI. Both toxins modified the same panel of small GTPases and exhibited similar in vitro autoprocessing kinetics. On the basis of sequence variations in the frizzled-binding domain (FBD), we reasoned that TcdBVPI and TcdBNAP1 might have different receptor specificities. To test this possibility, we used a TcdB from a NAP1 variant strain (TcdBNAP1v) unable to glucosylate RhoA but with the same receptor-binding domains as TcdBNAP1. Cells were preincubated with TcdBNAP1v to block cellular receptors, prior to intoxication with either TcdBVPI or TcdBNAP1. Preincubation with TcdBNAP1v blocked RhoA glucosylation by TcdBNAP1 but not by TcdBVPI, indicating that the toxins use different host factors for cell entry. This crucial difference might explain the increased biological activity of TcdBNAP1 in the intestine, representing a contributing factor for the increased virulence of the NAP1/027 strain.